(untitled) (International Seven Journal of Multidisciplinary, 2024)
Recent studies on sustainable urban paving solutions have focused on the use of permeable pavements and the integration of recycled materials, such as construction and demolition (C&D) waste. As urbanization increases, vegetated areas are being replaced by impermeable surfaces, causing negative impacts such as higher surface runoff and reduced water infiltration. Permeable pavements provide an efficient alternative, allowing water infiltration into the soil and contributing to flood mitigation and aquifer recharge. The use of recycled aggregates, such as recycled concrete and reclaimed asphalt, has gained attention because it reduces the demand for natural materials and minimizes the environmental impact of construction. However, the application of these materials still faces challenges, such as the variability of recycled waste, resistance issues, and the risk of pore clogging, which can impair long-term infiltration capacity. Recent studies indicate that the mechanical properties and durability of these pavements can be improved through techniques such as chemical stabilization and resin treatments. The lack of clear technical regulations and concrete economic data has limited the large-scale implementation of these systems, but ongoing research is helping to overcome these barriers. Standardizing testing methods, defining performance criteria, and establishing proper maintenance guidelines are crucial steps to ensure the widespread adoption of these solutions. Ultimately, the use of permeable pavements with recycled materials represents an effective strategy for promoting urban sustainability, reducing the environmental impact of construction, and improving the quality of life in cities.